Spatial-Temporal Response of Sediment Loads to Climate Change and Soil Conservation Practices in the Northern Aegean Watershed, Türkiye - Avcı, Bekir Cem; Kesgin, Erdal; Atam, Masume; Tan, Remziye İlayda (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Climate change and agricultural activities are significant sources of stress to the natural environment and water resources. These also affect erosion and the associated estimation of sediment yields, which is also a crucial task in the hydrological models. The presented study is significant for the development of sustainable watershed management practices. It also aims to determine the effects of climate change and different agricultural best management practices (BMPs) on the sediment loads of the North Aegean Basin in Türkiye by using the Soil and Water Assessment Tool (SWAT) model. While sediment calibration was performed for 2014, streamflow calibration and verification were performed using the SWAT Calibration and Uncertainty Program (SWAT-CUP) for the period 2012–2013 and 2014–2015, respectively. The obtained results showed that the climate change scenarios reduce the surface waters of the basin and sediment yield in accordance with the hydrological transport processes. During the 2012–2030 time period, runoff in the basin for the RCP4.5 and RCP8.5 climate change scenarios decreased by 38.5% and 31.8%, respectively, and the basin sediment yield decreased by 55.7% and 50.7%, respectively. The sediment yields to water resources had distinctive reductions due to BMPs such as zero tillage, vertical tillage, cover crop, and terracing. Considering the RCP4.5 and RCP8.5 scenarios, BMPs reduced the sediment yield in the range of 0.93–4.03% and 0.89–3.85%, respectively. Determining the sediment transport by using hydrological modeling and the effects of climate change for different agricultural practices on erosion will be useful for decision-makers.
Keywords: Soil Erosion; Sediment Yield; SWAT; Climate Change; BMP